2012
DOI: 10.1071/mf11169
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of exotic pine invasion on macroinvertebrate communities in southern Brazil coastal ponds

Abstract: Exotic pine invasion influences native wetland assemblages by changing environmental conditions such as hydrological regime and physicochemical characteristics. The expansion of cultivated pine has been a concern in southern Brazil and its impacts on aquatic biodiversity are poorly known. We tested the hypotheses that: (1) pine invasion decreases aquatic macroinvertebrate richness and abundance, modifying composition and macroinvertebrate functional feeding groups in ponds; and (2) β-diversity between natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…In southern Brazil, 90% of the wetland systems have already been lost mainly due to agriculture, and the remaining ones are still at high risk due to the expansion of rice fields and exotic Eucalyptus and pine plantation . Studies conducted in wetlands of LPNP have shown that pine plantation changed the hydroperiod of wetlands causing a negative effect on macrophytes (Rolon et al 2011), macroinvertebrates (Stenert et al 2012), amphibians (Machado et al 2012), and probably on rivulid populations.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Brazil, 90% of the wetland systems have already been lost mainly due to agriculture, and the remaining ones are still at high risk due to the expansion of rice fields and exotic Eucalyptus and pine plantation . Studies conducted in wetlands of LPNP have shown that pine plantation changed the hydroperiod of wetlands causing a negative effect on macrophytes (Rolon et al 2011), macroinvertebrates (Stenert et al 2012), amphibians (Machado et al 2012), and probably on rivulid populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even-aged and monoculture plantations over the successive rotations can result in loss of soil nutrients and suitable habitats for taxa living in natural forests (Ma et al 2000, Lin et al 2001, Erskine et al 2006, Larjavaara 2008, Chen et al 2009, Hartmann et al 2010, Xu 2011, Liao et al 2012, Zhou et al 2015. Also, these forest stands may alter soil physiochemical, biological properties, and affect water resources (Scott 2005, Stenert et al 2012. In a study, Yang et al (1998) Perspectives of plantation forests in China chemical activities of total and rhizosphere soil in a plantation forest were largely affected compared to the natural forest of Castanopsis kauakamii in Xinkou, Sanming city, Fujian province, China.…”
Section: Ecological Effects Of Plantationsmentioning
confidence: 99%
“…Más aun, esto no es concordante con la evidencia empírica existente para la zona, considerando el nivel promedio de precipitaciones anuales (Keller et al, 2016). Sin embargo, en regiones donde se implantan especies con alto consumo de recursos hídricos (por ejemplo, pino caribaea) si se detectaron déficits hídricos derivados de las plantaciones forestales (Scott, 2005;Stenert, Bacca, Moraes, Avila y Maltchick, 2012). En este sentido, la relevancia del impacto de la actividad forestal sobre la disponibilidad de agua en la zona se pudo observar en el hecho que a partir del año 2014, según la empresa estatal Aguas de las Misiones SE, al menos dos compañías del sector forestal (incluida Arauco Argentina SA) han comenzado a pagar por el consumo de agua subterránea, aunque no por el uso que se detecta en los pinares sino por lo utilizado en sus respectivos aserraderos.…”
Section: Discusión De Resultadosunclassified